DEVELOPMENT OF SCIENCE LEARNING ACHIEVEMENT AND ANALYTICAL THINKING FOR 3RD-YEAR HIGH SCHOOL STUDENTS BY CONSTRUCTIVIST LEARNING MODEL - Buaphan, Suphaporn; Boontongtherng, Poosit (Journal for Developing the Social and Community, 2023)
The purpose of this research is to :1) Finding the effectiveness of learning management according to the constructivist theory of 3rd-year high school students with the efficiency criteria of 80/80. 2) Compare the learning achievement in science of 3rd-year high school students who received instruction based on the constructivist theory with the criterion of 80%. 3) Compare the analytical thinking abilities of 3rd-year elementary school students before and after receiving instruction based on the constructivist theory. 4) study the satisfaction of 3rd-year high school students who received science instruction based on the constructivist theory. The sample group consists of 17 students from the 3rd year of secondary school at Baan Kae Witthayakom School, second semester of the academic year 2022. The students were selected using a Cluster Random Sampling method. The research tools used include: 1) management plan based on constructivist theory, 2) Measurement of learning achievement performance test, 3) Measurement of analytical thinking abilities, and 4) Satisfaction questionnaire. The statistical analysis employed includes mean, standard deviation, percentage, and t-tests (One Sample, Dependent Samples) The research findings revealed that 1) The efficiency of organizing science learning activities according to the constructivist theory by 3rd-year high school students is 86.27/83.53, which is higher than the established criteria. 2) 3rd-year high school students have achieved statistically significant higher learning achievement in science with a percentage higher than 80, at a significance level of .05. 3) 3rd-year high school students have significantly higher analytical thinking abilities after studying compared to before, at a significance level of .05. 4) 3rd-year high school students who have studied through science learning activities based on the constructivist theory are generally highly satisfied.